Different physical delivery systems: An important approach for delivery of biological molecules in vivo - Khavari, Afshin; Orafa, Zahra; Hashemi, Mehrdad; Habibzadeh, Noorieh; Bolhassani, Azam (Archives of Advances in Biosciences, 2016)
Delivery of exogenous materials such as nucleic acids, peptides, proteins, and drugs into cells is an important strategy in modern cellular and molecular biology. Recently, the development of gene carriers for efficient gene transfer into cells has attracted a great attention. Furthermore, lack of effective drug delivery is one of the major problems of cancer chemotherapy. Many physical methods have been studied to enhance the efficiency of gene and drug delivery. These strategies help to cross the materials from membranes including needle injection, photodynamic therapy, jet injection, gene gun, electroporation, hydrodynamic injection, laser, magnetofection, and tattooing. The physical systems improve the transfer of genes from extracellular to nucleus by creating transient membrane pores using physical forces including local or rapid systemic injection, particle impact, electric pulse, ultrasound, and laser irradiation. The recent optimization techniques of transdermal patches could improve the transdermal drug delivery through the skin. Among different physical carriers, electroporation and gene gun are the most potent methods for gene transfection and drug delivery in vivo. However, the researchers have focused on enhancing their potency with the structural modifications. Regarding to numerous barriers for biomolecules delivery in cells, this review is concentrated on description and optimization of different physical delivery systems for gene or drug transfer across membrane.